Liberalization, stabilization and poverty in Latin America during the 1990s - André Urani (Institute for Applied Economic Research (ipea), 2015)
Latin America's lost decade seems to be definitely over. During the first half of the 1990's, GDP growth was higher than during the 1980's as a whole, at the same time than inflation was substantially reduced and poverty indicators progressively improved. These common trend tend to hide, however, important cross-country differences in the timing and in the nature of the structural reforms and of the stabilization policies that were at the origins of this process, and therefore of their macroeconomic and social impacts. The purpose of this paper is to study the recent experience of four among the main countries of the continent: Argentina, Brazil, Chile and Mexico. I start describing their macroeconomic policies and performances since the beginning of the 1990's. Then, I analize the impacts of the macroeconomic behaviour on the labor market and on income distribution. Finally, I try to investigate which kind of policies would be apropriated in order to reduce poverty faster then during the last years.
Keywords: 330